Pesticide removal from industrial effluents using biopolymeric materials - Sanchez, Laura Mabel; Ollier, Romina Paola; Pereira, Anderson Espirito Santo [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Alvarez, Vera Alejandra (Elsevier, 2020)
Associated with the growth of the human population and the development of the chemical industry, pesticides have been increasingly used for the control of pests in agriculture. As a result, these chemicals are now frequently found in water bodies and industrial wastewater. Therefore there is an evergrowing need to develop materials capable of removing such pollutants from water bodies. Materials with potential for this purpose include biopolymers such as chitosan, cellulose, starch, gums, and cyclodextrins. This chapter presents an overview of pesticides and their fates in the environment, together with examples of biopolymers and their potential applications in the removal of pollutants from water resources. However, in literature, there are only few studies reporting the use of biopolymeric membranes to remove industrial effluents, and, in this way, we have also considered other examples such as biopolymeric particles and treatment of pesticides. It could be concluded from the analysis undertaken that biopolymers have great potential for wastewater treatment, although there are still challenges associated with scale-up and the need for pilot studies before products based on biopolymers can reach the marketplace.
Keywords: Biopolymers; Effluent treatment; Membranes; Pesticides